ENHANCEMENT OF JUNIOR HIGH SCHOOL STUDENTS’ CONCEPT COMPREHENSION IN HYDROSTATIC PRESSURE AND ARCHIMEDES LAW CONCEPTS BY PREDICT-OBSERVE-EXPLAIN STRATEGY (Jurnal Pendidikan IPA Indonesia, 2016)
This study explored effectiveness of Predict-Observe-Explain (POE) strategy to enhance concept comprehension of junior high school students in hydrostatic pressure and Archimedes law concepts. Subjects of this study were 31 students of a private junior high school in East Flores in even semester year 2015/2016. By mixed-method design, this study concluded that (1) average score of concept comprehension was significantly increase (p = 0.000) from pre-test (36.77) to post-test (63.26) with strong category of effect size (1.62), and moderate category of N-gain (0.40); (2) learning was also succeed identifying some misconceptions and remedied it. Those misconceptions were: (a) hydrostatic pressure was influenced by liquid volume and or the shape of the container, (b) an object was floated for there was air within, (c) a sunken object had no buoyant force, and (d) the magnitude of buoyant force was equal to liquid volume; (3) some of common problems around the students in applying hydrostatics concept and buoyant force were as follow (a) related to mathematical representation of hydrostatic force Ph = P0 + ?gh, most all students interpreted h as the depth measured from the bottom of the liquid column (not from the surface of the liquid as it should be), (b) related to buoyant force, the problem depended on the context where the question given. In context of immovable objects in a certain fluid, almost all student was hard comparing buoyant force magnitude to the weight. In context of sliding object in liquid, almost all students failed to explain the object position to its buoyant force.